Trincheirias de infiltração: experimento da aplicação na área da UTFPR - câmpus Londrina - Puzzi, Liliana Cristina Malmegrin (2015)
Hydrological and environmental impacts can be generated by the lack of infrastructure and planning the use and occupation of land, the intensification of urbanization processes thus resulting in higher peak flows. Aiming to evaluate the use of drainage methods, this paper aims a trench infiltration. Through a water balance, estimating input flows, tried to verify its efficiency by the amount of infiltration volume and the volume stored in a time interval. The results showed that for the same soil type, the type being theoretically clayey, has different values in the infiltration rate. With the infiltration rate was possible to estimate different values in the length dimension of the trench, ranging from 1.8 to 1.2 meters to a flow rate of 35.65 L / min. It was efficient to use Arduino system, through a distance sensor in order to increase the accuracy of the results towards the infiltration rate, which is calculated by the infiltrated volume divided by percolation area. The conclusion is the importance of soil characterization, through the physical indices such as particle density (2.86 g / cm³), bulk density (1.16 g / cm³), porosity (59.5%) and moisture to investigate the possibility of installing the device, and correlations with soil clay-like. As the filler material, the porosity by containing gravel being greater than or equal to 50%. With the use of Guelph permeameter, allows to obtain values for the hydraulic conductivity, which was 5,501.10-5m / s being an important parameter because it has good possibility of infiltration into the soil.